The Influence of Age on The Attractiveness of Online Advertising and Brand Awareness of Tokopedia - Nabilah Nisrina (Jurnal Indonesia Sosial Teknologi, 2024)
This research activity aims to analyse the influence of age on Tokopedia's brand awareness and the attractiveness of Tokopedia's online advertising to the audience. The research methodology used is a quantitative approach with survey methods. The survey acquisition data is then processed using the SPSS application. The results showed that the age variable did not significantly influence Tokopedia's brand awareness or the attractiveness of Tokopedia's online advertising to the audience. This study concludes that technological developments also have an impact on bringing progress and development in various fields. The Industrial Revolution 4.0, limited mobility due to the pandemic, and the discourse on the application of Society 5.0 have also encouraged the development of the internet and technology and its application to various aspects of life and the work sector.